Registration of 'S15‐10434C' soybean cultivar with high yield, resistance to multiple diseases, and wide adaptation. Issue 2 (11th April 2022) - Chen, Pengyin; Ali, M. L.; Shannon, Grover; Crisel, Melissa; Smothers, Scotty; Clubb, Michael; Selves, Stewart; Canella Vieira, Caio; Lee, Dongho; Scaboo, Andrew; Usovsky, Mariola; Nguyen, Henry T.; et al.
Abstract: 'S15‐10434C' (Reg. no. CV‐548, PI 699630) is a maturity group V, high‐yielding conventional soybean [ Glycine max (L) Merr.] cultivar developed and released in 2019 by the University of Missouri–Fisher Delta Research Center Soybean Breeding Program. S15‐10434C was developed following conventional breeding from a cross between 'S11‐17025C' and 'S11‐14954', which are Missouri soybean lines. 'S11‐17025C' is a high‐yielding cultivar with resistance to multiple diseases, and 'S11‐14954' is a line with high yield potential and soybean cyst nematode resistance developed by the University of Missouri soybean breeding program. Before release, S15‐10434C was tested in 107 environments in Missouri and other southern states from 2016 to 2019 for yield and other agronomic traits. On average, S15‐10434C yielded 4, 102 kg ha –1, which is higher than the all‐tests mean of 3, 907 kg ha –1 . S15‐10434C seed contains 40.7% protein and 21.7% oil on a dry‐seed‐weight basis. It exhibits relative maturity of 5.5, determinate growth habit, purple flowers, tawny pubescence, and tan pod wall. Seeds are yellow with intermediate luster and black hila, with seed weight of 13.1 g 100 –1 seed. S15‐10434C is 76 cm tall and has resistance to lodging. It is resistant to cyst nematode (races 1, 2, 3, 5, and 14), reniform nematode, peanut and southern root knot nematodes, sudden death syndrome, and frogeye leaf spot and has field tolerance to phytophthora root rot. It is also a chloride excluder. In addition to its high yield potential and desired seed protein content, S15‐10434C has broad adaptation across southern states. Core Ideas: Cultivated soybean is a major oil seed crop and major source of protein. Diseases, such as SCN, RN, RKN, FLS, and SDS can cause significant yield losses every year. We developed a high‐yielding soybean cultivar with broad disease resistance. The released cultivar has desired protein and broad adaptation in U.S. southern states. The released cultivar is a non‐GMO soybean that may offer a premium price to growers.